P061 Association between work related stress and qt prolongation in male workers: the role of low job control. (1st September 2016) - Lecca, Luigi Isaia; Piazza, Maria Francesca; Fabbri, Daniele; Ursi, Michela; Serra, Tiziana; Garofalo, Elisabetta; Portoghese, Igor; Meloni, Michele; Cocco, Pierluigi; Campagna, Marcello
Abstract : Introduction: Several studies have shown that high demand and low control jobs are associated with poor physical and mental wellbeing. Aim of our study was to test the association between job strain and the QTc interval on the electrocardiogram, an indicator of autonomic function, blood pressure, body mass index (BMI), and fasting glycaemia level. Methods: Overall 280 male workers of a logistic support company for secure communication and intelligence were included in our study population. We measured work-related stress using the HSE indicator tool, general wellbeing using the Well-being Index (WHO5); affectivity was measured by the short version of the positive and negative affect schedule (PANAS); the frequency corrected QT (QTc) interval on the electrocardiogram was measured using the Bazett's formula; QT index (QTi) value, blood pressure, BMI, and fasting glycaemia were also recorded, as well as medications, lifestyles and comorbidities. Based on the Karasek's taxonomy, we compared high strain jobs, low strain jobs, active jobs and passive jobs with respect to WHO5, PANAS, QTc, QTi, blood pressure, BMI and glycaemia. Group differences were analysed by means of parametric and non parametric tests. Results: Results showed that low strain jobs were associated with a lower frequency of negative affectivity than high strain jobs (Fisher test = 3.63, p < 0.05). Employees with passive jobs (low demand and low control) showed a significantly longer QT index than workers in high-strain jobs (high demand and low control) (F = 3.18, p < 0.05). No significant differences were found among the four groups on the other investigated variables. Conclusions: In our study population, we did not observe a reduction in cardiac vagal control, as indicated by a prolonged QTi, among subjects employed in high strain and low control jobs.